2011
DOI: 10.1088/0957-4484/22/26/265505
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanostructured iron oxide–gold bioelectrode for hydrogen peroxide sensing

Abstract: Fe(3)O(4) nanoparticles covalently linked to a gold electrode have been used for immobilizing catalase (CAT) enzyme to sense the presence of various concentrations of H(2)O(2). These nanoparticles ranging from 20 to 30 nm were synthesized by thermal co-precipitation of ferric and ferrous chlorides. SEM and XRD have been used for morphological and structural characterization of Fe(3)O(4) nanoparticles. CAT enzyme was linked covalently to the surface of iron oxide using carbodiimide in phosphate buffer (pH 7.4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…For ALW and BHW samples the measured relative coverage are 0.28 and 0.19 respectively, a ratio of 1.55. Thanvadan et al 33 have observed similar H 2 O 2 oxidation behaviour with an enzyme promoted nanoparticulate Fe 3 O 4 system whereas in this study no enzyme and other treatments were used for H 2 O 2 detection.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…For ALW and BHW samples the measured relative coverage are 0.28 and 0.19 respectively, a ratio of 1.55. Thanvadan et al 33 have observed similar H 2 O 2 oxidation behaviour with an enzyme promoted nanoparticulate Fe 3 O 4 system whereas in this study no enzyme and other treatments were used for H 2 O 2 detection.…”
Section: Resultssupporting
confidence: 58%
“…We would argue this shows that this chemistry can be exploited in a range of fields and applications. The sensitivity and detection limit for this linear range of concentrations for both H 2 O 2 and EtOH is more efficient than previously reported works 33 35 39 42 .…”
Section: Discussionmentioning
confidence: 61%
“…Metallic NPs (e.g., Au, Ag, Cu, Pd, Co, Pt, etc) possess a range of fascinating properties (localized surface plasmon resonance (LSPR) and surface-enhanced Raman scatting (SERS)) [ 245 ] and many anisotropic metallic NPs have been applied in catalysis [ 246 ], contrast imaging [ 247 ], medicine [ 248 ], and sensing [ 249 ]. The combination of metallic NPs and magnetic IONPs has also attracted increasing interest to materials scientists due to their combined physicochemical properties and potential properties in catalysts [ 250 ], biotechnology [ 251 ], and biomedicine [ 252 , 253 ]. Generally, monodispersed iron oxide/metal nanostructures, such as core–shell, core–satellites, and dumbbell structures, exhibit binary/polynary properties.…”
Section: Surface Functionalization Of Magnetic Ionpsmentioning
confidence: 99%
“…Iron oxide (Fe 3 O 4 ) nanoparticles are attractive candidates as nanointerfaces for sensing applications due to their biocompatibility, high surface area-to-volume ratio and excellent electron transfer characteristics [27]. Our earlier work on the development of a H 2 O 2 sensor utilizing catalase and iron oxide confirmed the promising effect of iron oxide nanoparticles as a nanointerface [23]. Carbon nanotubes (CNTs) are another category of nanomaterials that are well explored for their excellent electron transfer properties in electrode modification and biosensor field.…”
Section: Introductionmentioning
confidence: 80%
“…A wide variety of biosensors has been reported that utilizes a single nanointerface namely ceria, gold nanoparticles, multi-walled carbon nanotubes and iron oxide [20][21][22][23]. A nanointerface unites the activity of the sensing element in a spatial manner and it results in a sharp signal.…”
Section: Introductionmentioning
confidence: 99%